Cultivating an ethic of wellness in Geography. (8th June 2016) - Mullings, Beverley; Peake, Linda; Parizeau, Kate
Abstract : Drawing upon recent initiatives to highlight issues of mental health in the academy we focus in this special issue on work by geographers from Canada, the United States, England, and New Zealand that aims to shed some light on the ways that the organized practices of the academy are implicated in the current state of mental health of a broad cross section of its members across university campuses. In bringing the perspectives of Geography graduate students and faculty to bear on questions of mental wellness, this special issue is unique in its attempt to bring together three bodies of research: geographers' understanding of the relationship between mental and emotional health, social space, and material places; mental health initiatives in institutions of higher education; and the neoliberalization of the academy. Drawing together review articles, interview‐based research, collective writing, and personal narratives, the articles and viewpoints bring together understandings of the crisis of mental health and wellbeing in neoliberalizing universities, and institutional and individual responses. Réflexions critiques sur la formation d'une éthique du bien‐être en géographie: Prenant appui sur les démarches entreprises récemment pour mettre en évidence les problèmes de santé mentale dans le milieu universitaire, ce numéro spécial se consacre aux travaux effectués par des géographes en provenance du Canada, des États‐Unis, de l'Angleterre et de la Nouvelle‐Zélande afin de jeter un éclairage sur le rapport entre les modes d'organisation du milieu universitaire et l'état actuel de santé mentale d'un vaste échantillon du personnel en poste dans plusieurs campus universitaires. En dégageant les perspectives des étudiants des cycles supérieurs et des professeurs en géographie qui se penchent sur le bien‐être mental, ce numéro spécial innove en proposant une synthèse de trois champs de la connaissance scientifique : la compréhension par les géographes de la relation qui unit la santé mentale et émotionnelle, l'espace social et les lieux physiques ; les actions en santé mentale dans les établissements d'enseignement supérieur ; et la montée en puissance du néolibéralisme dans le milieu universitaire. Composé d'articles de fond, de recherches reposant sur des entrevues, d'ouvrages collectifs et de récits personnels, ce recueil propose une série d'articles et de points de vue qui exposent une diversité d'idées sur la crise en santé mentale et bien‐être dans un contexte universitaire marqué par le néolibéralisme, et sur les mesures prises par les établissements et les individus. Key Messages: There is a crisis of mental health in the academy. This special issue, the first to address this crisis, brings together three bodies of research: geographers' understanding of the relationship between mental health, social space, and material places; mental health initiatives in higher education; and the neoliberalization of the academy. In this introduction we discuss two particular foci: defining the crisis of mental health and wellbeing in neoliberalizing universities, and institutional and individual responses. Watch a video presentation of this Special Issue